Anti-blast analysis and design of a sacrificial cladding with graded foam-filled tubes. (January 2023) - Zhang, Hao; Chang, Baixue; Peng, Kefeng; Yu, Jilin; Zheng, Zhijun
Abstract: Foam-filled tubes are excellent energy absorption structures for impact resistance, and graded foam may have superiority for the design of anti-blast sacrificial cladding. The anti-blast response of density-graded foam-filled tubes as a core layer is investigated numerically and theoretically. Mesoscopic finite element models for graded foam-filled tubes are constructed, and their constant-velocity compression and anti-blast performance are simulated. One-dimensional analytical shock models based on an empirical force–displacement relationship are developed to analyze the axial collapse wave propagation in graded foam-filled circular tubes. Single-/double-wave deformation patterns are observed for graded foam-filled tubes under blast loading, especially the negatively graded foam-filled tubes with gradient parameters close to zero may also show a single-wave deformation pattern. The results demonstrate that the negatively graded foam-filled tube with a small density gradient is a good choice to design anti-blast sacrificial cladding with a small critical length and a low transmitted force. A contour map of the critical length required to absorb the impulse of blast loading for different gradient parameters and diameter-thickness ratios of the outer tube is established. This study proposes a new design guideline for superior blast resistance structures in engineering applications. Highlights: A sacrificial cladding design strategy with graded foam-filled tubes is proposed. Mesoscopic finite element models for graded foam-filled tubes are constructed. Deformation patterns for graded foam-filled tubes under blast loading are distinguished. Anti-blast analytical models according to single/double-wave features are established. A guidance scheme for the design of critical thickness of sacrificial cladding is presented.